1997
DOI: 10.1007/s004380050342
|View full text |Cite
|
Sign up to set email alerts
|

The 28.5-kDa iron-sulfur protein of mitochondrial complex I is encoded in the nucleus in plants

Abstract: The intrinsic 28.5-kDa iron-sulfur protein of complex I in the mitochondrial respiratory chain is encoded in the nucleus in animals and fungi, but specified by a mitochondrial gene in trypanosomes. In plants, the homologous protein is now found to be encoded by a single-copy nuclear gene in Arabidopsis thaliana and by two nuclear genes in potato. The cysteine motifs involved in binding two iron-sulfur clusters are conserved in the plant protein sequences. The locations of the seven introns, with sizes between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The low signal detected, probably because of imperfect fit between the N. sylvestris sequence and the potato primers, indicates that the quantification was not perturbed by the expression of an endogenous NADPH dehydrogenase gene. The 28.5 kDa subunit of tobacco complex I (Schmidt‐Bleek et al ., 1997) was used as control, showing similar transcript levels in transformants and WT plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low signal detected, probably because of imperfect fit between the N. sylvestris sequence and the potato primers, indicates that the quantification was not perturbed by the expression of an endogenous NADPH dehydrogenase gene. The 28.5 kDa subunit of tobacco complex I (Schmidt‐Bleek et al ., 1997) was used as control, showing similar transcript levels in transformants and WT plants.…”
Section: Resultsmentioning
confidence: 99%
“…(2002). The primer sequences used for real time PCR were for St‐ NDB1: 5′‐AGAGCGAAGGACCAACCTCC‐3′, 5′‐ACAACCCTTCACTCGCAACC‐3′, and for the N. tabacum 28.5 kDa subunit of complex I (Accession number ; Schmidt‐Bleek et al ., 1997): 5′‐TCGTCAGCTTGTTTTGCCAG‐3′, 5′‐GGCTTCTTGGCAGAATCCAC‐3′. RT‐PCR for screening of transgenic lines was performed using primers St‐ – S1: 5′‐GCATAGTAGAGCCGGTTCGG‐3′, 5′‐TTTCCTGGCCAACTTGTTCC‐3′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high degree of structural conservation of the iron-sulphur and NADH-binding protein subunits between bacteria, protozoa, fungi and mammals suggests these proteins are essential components for a functional respiratory chain. For plants, genes coding for three of these central intrinsic subunits have recently been identified Heiser et al, 1996;Schmidt-Bleek et al, 1997). These plant homologues for the mammalian 51 kDa subunit (the NADH-binding protein, 55 kDa) and two intrinsic ironsulphur proteins (PSST, 22 kDa and TYKY, 28 kDa) are encoded by nuclear genes (nuclear-encoded Complex I genes, nCI genes).…”
Section: Introductionmentioning
confidence: 99%
“…In mature rice plants, high relative amounts of IF 1 -1 and IF 1 -2 transcripts were detected in the young panicles and the panicles after heading in comparison with in the leaf blades and leaf sheaths. High levels of expression in¯owers (panicles) have been observed for the genes coding the mitochondrial respiratory proteins in other plant species such as tobacco, potato, sun¯ower and Arabidopsis thaliana (Huang et al 1994;Smart et al 1994;Heiser et al 1996;Schmidt-Bleek et al 1997) as well as rice (Ohtsu et al 1999). Based on these ®ndings, it has been suggested that the energy produced by the mitochondrial oxidative phosphorylation is needed during the generative¯oral life cycle.…”
Section: Resultsmentioning
confidence: 99%